Instrument validation of perceived organizational support (POS) indonesian version: A rasch model analysis - Wahyu Syahputra; Devie Yundianto; Edwin Indrawardhana (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
The Perceived Organizational Support scale developed by Eisenberg is still quite widespread in Indonesia. The POS scale precisely measures how employees perceive organizational support. On the other hand, analysis of items on the POS scale continues. However, this scale analysis has yet to be found using the Rasch Model with a sample of Indonesian people. One of the advantages of the Rasch model is objectivity-specific, i.e., item parameters do not depend on individual characteristics, and vice versa. So this study aims to analyze the validity of the items using the Rasch model. The sample in this study consisted of 325 people consisting of 175 men (52.31%) and 150 women (47.69%). The age range of 18 years – to 68 years. From the item validation test, this scale has good unidimensionality, a standardized reliability index so that the scale is reliable enough, and has items that fall into the fit proper test criteria. The conclusion is that the POS scale has good potential to measure Perceived Organizational Support in Indonesia.